2016
DOI: 10.1136/tobaccocontrol-2015-052804
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco price increase and smoking behaviour changes in various subgroups: a nationwide longitudinal 7-year follow-up study among a middle-aged Japanese population

Abstract: ObjectiveFew longitudinal studies have examined the effect of tobacco price increase on both cessation among smokers and relapse among quitters. Our objective was to investigate the differential impact of the tobacco price increase on the changes in smoking status in the total population and various subgroups.MethodsWe analysed data from a Japanese nationally representative longitudinal study of 30 773 individuals aged 50–59 years (weighted sum of discrete-time number = 215 411) with smoking information, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
1
31
2
Order By: Relevance
“…58,1012,49 Only two longitudinal studies have previously examined the association of cigarette prices with smoking relapse. 51,52 Those studies found higher prices were negatively associated with relapse, in contrast to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…58,1012,49 Only two longitudinal studies have previously examined the association of cigarette prices with smoking relapse. 51,52 Those studies found higher prices were negatively associated with relapse, in contrast to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, smoking was found to have a strong and dose‐independent effect on the risk of death before lung cancer occurrence, which translated into higher 10‐year cumulative probabilities of death in smokers (eg, approximately 30% in smokers vs 19% in never‐smokers for men aged 70 years). Given that smoking is a modifiable risk factor with a strong impact on health, this finding emphasizes again the need for better strategies for smoking control at both the individual level (information and prevention campaigns) and institutional level (eg, promotion of tobacco‐free public places and control of cigarette prices) …”
Section: Discussionmentioning
confidence: 99%
“…Given that smoking is a modifiable risk factor with a strong impact on health, this finding emphasizes again the need for better strategies for smoking control at both the individual level (information and prevention campaigns) and institutional level (eg, promotion of tobacco-free public places and control of cigarette prices). 6,30 In addition to the role of smoking history, age at start of followup was also found to have a substantial impact on lung cancer occurrence, with a differential effect between genders, the risk increasing more steeply in older men than in older women. This translates into a higher incidence of lung cancer in older men for a given level of exposure to other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, a study by Burton, Clark, Heuler, Bollerup and Jackson (2011) found that heavy smokers bought their tobacco products from outlets that offered a lower price, while lighter smokers used outlets that were more convenient for them. In Japan, a study by Tabuchi, Fujiwara and Shinozaki (2017) found that price increase affected various subgroups but not heavy smokers or the recently unemployed.…”
Section: Consumer Reactions To Price Increasementioning
confidence: 99%